Springgay, S. & Truman, S. E. 2018. Walking Methodologies in a More-than-Human World: WalkingLab. London: Routledge - van Eeden-Wharton, Adrienne (Critical Studies in Teaching and Learning, 2023)
Stephanie Springgay and Sarah E. Truman’s Walking Methodologies in a More-than-Human World: WalkingLab, is not a book about walking. Rather, it is a walking-writing of itinerant and entangled concepts and a thinking-in-movement-with the collaborative research-creation events hosted by WalkingLab.1 The book makes a significant, refreshing contribution to the burgeoning body of international scholarship that advocates that academic inquiry not only can – but must – be done differently. Springgay and Truman’s walking-writing troubles the tacit (often-unchecked) anthropocentrism, individualism, neoliberalism, ableism, and ongoing legacies of settler colonialism and onto-epistemic violence that proliferate in Euro-Western conceptions of, and scholarship on, walking. Following Juanita Sundberg’s discussion of walking with, they advocate a shift to walking praxis that is relational, attentive, and ethically and politically accountable.2 This is particularly apposite within the context of the fraught South African body politic where mobility and access remain vastly unequal, and many walking bodies are marked by precarity, violence, and erasure